1986
DOI: 10.1007/bf01369977
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of apparent slip flow of polymer solutions

Abstract: Abstract:The apparent slip flow phenomenon of polymer solutions in capillary tubes is analyzed by a thermodynamic diffusion model. An approximate solution of the developing concentration profiles shows a significant decrease in the polymer wall concentration. The approximate concentration profiles are coupled with the concentration-dependent viscosity for aqueous polyacrylamide solutions to provide a priori predictions of the magnitude of the effective slip velocity at the wall. The results are in a reasonable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
(68 reference statements)
1
33
0
Order By: Relevance
“…The correlation for slip proposed by Cohen & Metzner [41,42] for a power law Ostwald fluid can be adapted for a viscoplastic Herschel-Bulkley fluid. This leads to the following equation for the slip volumetric flow rate (Q s ) as a function of the apparent volumetric flow rate (Q): The slip velocity is taken as an empirical power function of the wall shear stress according to Eq.…”
Section: Slip Corrected Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…The correlation for slip proposed by Cohen & Metzner [41,42] for a power law Ostwald fluid can be adapted for a viscoplastic Herschel-Bulkley fluid. This leads to the following equation for the slip volumetric flow rate (Q s ) as a function of the apparent volumetric flow rate (Q): The slip velocity is taken as an empirical power function of the wall shear stress according to Eq.…”
Section: Slip Corrected Measurementsmentioning
confidence: 98%
“…The slip phenomenon has been widely described in lots of articles [39][40][41][42][43][44][45] and is known to be due to a drop in solid concentration close to the moving geometry or close to the wall in the case of pipes. The presence of a less concentrated thin layer of lower viscosity close to the wall induces, for a given shear stress a local enhancement of the shear rate.…”
Section: Raw Measurementsmentioning
confidence: 99%
“…7,8) For non-Newtonian fluids many papers also have been already published. [9][10][11][12][13][14][15][16][17][18][19][20] Migler et al 9) directly measured the local velocity of a sheared polymer melt within 100 nm from the solid surface using evanescent light. They reported that polymers slip at all shear stresses in the absence of strong polymer absorption.…”
Section: Introductionmentioning
confidence: 99%
“…55,56,75,84,111,120 In some systems, such as microfluidic and viscoplastic, and over certain deformation rate regimes the contribution of wall slip to the total flow rate could be substantial. 23,31,43,55,56,75,84,111,120 In some extreme cases of plug flow, the flow is totally due to wall slip and hence the fractional flow rate becomes unity.…”
Section: Introductionmentioning
confidence: 99%
“…Slip analysis was pioneered by Mooney 100 who proposed the method of using flow curves from tubes of different sizes to detect and quantify slip. 13,31,54,64,84,101 Wall slip is a very complex phenomenon with no well-developed theory to explain it in its variety 88 and provide accurate predictions with solid experimental foundation. One reason is the difficulty of direct observation and measurement of slip.…”
Section: Introductionmentioning
confidence: 99%